Multiwavelength Analysis of GRB 250101A: From Gamma-Ray Prompt Emission to Optical Afterglow - Guowang Du; Yehao Cheng; Yuan-Pei Yang; Jun Yang; Jinghua Zhang; Dan Zhu; Yu Pan; Yuan Fang; Xingzhu Zou; Brajesh Kumar; Helong Guo; Xufeng Zhu; et al. (The Astrophysical Journal, 2025)
The interaction between the relativistic jet and the circumburst medium produces a multiwavelength afterglow of a gamma-ray burst (GRBs). In this work, we present multiwavelength properties of GRB 250101A based on the observations of Swift, Fermi, and Mephisto. The spectral analysis of Swift/Swift Burst Alert Telescope (BAT) and Fermi/Gamma-ray Burst Monitor (GBM) reveals a soft prompt spectrum with a low-energy photon index of −1.18 and a peak energy of 33 keV, and the isotropic energy is 1.4 × 10 ^52 erg. The prompt emission of GRB 250101A aligns with Type II GRBs in the Amati relation. Meanwhile, our analysis indicates that GRB 250101A is an X-ray-rich or X-ray-dominated GRB, with intrinsic properties suggesting that it is relatively softer than most classical GRBs. Optical observation with Mephisto, beginning 197 s post-trigger, shows a single power-law decay in uvgriz bands, with F _ν _,obs  ∝  t ^−0.76 ν ^−1.21 . The observed spectral index significantly exceeds theoretical predictions under standard afterglow models, suggesting a color excess of ∼0.216 mag. However, combining X-ray and optical afterglow, we find that GRB 250101A is more likely a “normal burst” rather than an “optical-dark burst,” and the dust extinction effect plays an important role in the optical blue bands. Furthermore, there is a structural change at T _0  + 2924 s in the optical light curve, indicating a density drop of ∼50% in the interstellar medium at a distance of ∼0.13 pc. Our analysis shows that this GRB clearly shows some unique characteristics in its observed X-ray-rich prompt emission as well as the circumburst environment, implying a special progenitor.